The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.cell.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-Erk-ETS-Signaling Pathway Is a Drug Target for Longevity

Abstract: SummaryIdentifying the molecular mechanisms that underlie aging and their pharmacological manipulation are key aims for improving lifelong human health. Here, we identify a critical role for Ras-Erk-ETS signaling in aging in Drosophila. We show that inhibition of Ras is sufficient for lifespan extension downstream of reduced insulin/IGF-1 (IIS) signaling. Moreover, direct reduction of Ras or Erk activity leads to increased lifespan. We identify the E-twenty six (ETS) transcriptional repressor, Anterior open (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
193
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 54 publications
(70 reference statements)
6
193
1
2
Order By: Relevance
“…Such an approach has previously been employed for the Hnrnpa1 and Hnrnpa2b1 genes where upregulation of the Hnrnpa1 gene or the Hnrnpa2 isoform of the Hnrnpa2b1 gene in mouse hepatocarcinoma cells was shown to cause activation of the RAS‐MAPK‐ERK pathway (Shilo et al ., 2014). This is potentially important since a recent study has shown that activation of the RAS‐ERK‐ETS pathway is a key determinant of lifespan in Drosophila species (Slack et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Such an approach has previously been employed for the Hnrnpa1 and Hnrnpa2b1 genes where upregulation of the Hnrnpa1 gene or the Hnrnpa2 isoform of the Hnrnpa2b1 gene in mouse hepatocarcinoma cells was shown to cause activation of the RAS‐MAPK‐ERK pathway (Shilo et al ., 2014). This is potentially important since a recent study has shown that activation of the RAS‐ERK‐ETS pathway is a key determinant of lifespan in Drosophila species (Slack et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Cancers with constitutively activated MAPK signaling exhibit elevated ERK-dependent transcriptional output, and inhibition of this output is correlated with a therapeutic response to targeted therapies (10,11). While one characterized mode of transcriptional regulation is direct ERKmediated phosphorylation of transcription factors (12)(13)(14), other mechanisms that dynamically couple ERK activity and modulate the nuclear transcriptional output response in ERK-dependent cancers have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…5 We found that selective inhibition of signaling through either of these pathways increased longevity. Moreover, direct genetic inhibition of Ras or Erk extended lifespan through activation of the E-twenty six (ETS) transcription factor, Anterior Open (AOP).…”
Section: Submit Your Article To This Journalmentioning
confidence: 87%
“…5 Hyperactivation of the Ras oncogene is believed to be responsible for around 30% of all human tumors. The Ras proteins function as small GTPases, cycling between inactive GDP-bound and active GTP-bound states to transmit signals from receptor tyrosine kinases (RTKs).…”
Section: Submit Your Article To This Journalmentioning
confidence: 99%